2017
DOI: 10.1371/journal.pone.0178785
|View full text |Cite
|
Sign up to set email alerts
|

Polydim-I antimicrobial activity against MDR bacteria and its model membrane interaction

Abstract: The rapid spread of multi-drug resistant pathogens represents a serious threat to public health, considering factors such as high mortality rates, treatment restrictions and high prevalence of multi-drug resistant bacteria in the hospital environment. Antimicrobial peptides (AMPs) may exhibit powerful antimicrobial activity against different and diverse microorganisms, also presenting the advantage of absence or low toxicity towards animal cells. In this study, the evaluation of the antimicrobial activity agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Natural small molecules from the extract of herbs and spices have shown good antibacterial effects, , and thymol is one among them, a monoterpene phenol found in the oil of plants from the Lamiaceae family. , It has also been found that thymol in synergy with synthetic antibiotics decreases antibacterial resistance . There are many reports available on the action of antimicrobials and small molecules on live bacteria as well as model phospholipid membrane systems. Despite these investigations, microscopic insights into the preferred pathways for molecules to cross the outer membrane (OM) are not well explored. In order to understand the origins of the resistance to the translocation of small molecules across the bacterial cell envelope, it is not sufficient to create realistic in vitro bacterial membrane platforms but also devise means to determine the transport of molecules across the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Natural small molecules from the extract of herbs and spices have shown good antibacterial effects, , and thymol is one among them, a monoterpene phenol found in the oil of plants from the Lamiaceae family. , It has also been found that thymol in synergy with synthetic antibiotics decreases antibacterial resistance . There are many reports available on the action of antimicrobials and small molecules on live bacteria as well as model phospholipid membrane systems. Despite these investigations, microscopic insights into the preferred pathways for molecules to cross the outer membrane (OM) are not well explored. In order to understand the origins of the resistance to the translocation of small molecules across the bacterial cell envelope, it is not sufficient to create realistic in vitro bacterial membrane platforms but also devise means to determine the transport of molecules across the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, CTLA-4-targeted scFv-melittin fusion protein acts as a potential immunosuppressive agent showed selective cytotoxicity assist in organ transplants [76]. Melittin coupled to avidin, when released induces immediate cell lysis [77] and stop cancer cell latency [78]. Asterosaponin 1 is isolated from starfish Culcitano vaeguineae.…”
Section: Anti-proliferative Activitymentioning
confidence: 99%
“…In addition, CrTX displayed anti-angiogenic effects in vivo [85]. Snake venom-derived drug cerivastatin also reduces the proliferation and invasion of aggressive breast cancer cells [86]. DisBa-01, a low molecular weight recombinant protein, specifically interacted with alpha(v)beta3 integrin and shows potent anti-metastatic and anti-angiogenic properties.…”
Section: Anti-proliferative Activitymentioning
confidence: 99%
“…The peptide prevents bacterial growth through the inhibition of protein synthesis, did not result in visible morphological changes. Polydim-I treatment at 2 mg/kg/mLW showed significant reduction of the bacterial load in in the lungs, spleen, and liver [ 15 ], and the antimicrobial properties against S. aureus , E. coli , Enterococcus faecalis , Acinetobacter calcoaceticus-baumannii were displayed with MIC 50 values of 4.1, 50.7, 73.2, and 84.0 μg/mL, respectively [ 73 ].…”
Section: Biological Properties Of Wasp Venom and Their Isolated Amentioning
confidence: 99%